2019
DOI: 10.3390/ijms20153744
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiated Endometrial Carcinoma Could be A Target for Immune Checkpoint Inhibitors (Anti PD-1/PD-L1 Antibodies)

Abstract: Dedifferentiated endometrial carcinoma (DDEC) is defined as an undifferentiated carcinoma admixed with differentiated endometrioid carcinoma (Grade 1 or 2). It has poor prognosis compared with Grade 3 endometrioid adenocarcinoma and is often associated with the loss of mismatch repair (MMR) proteins, which is seen in microsatellite instability (MSI)-type endometrial cancer. Recent studies have shown that the effectiveness of immune checkpoint inhibitor therapy is related to MMR deficiency; therefore, we analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Given the expanded indication for immunotherapy of MMR protein‐deficient tumors, immune check point inhibitors may be considered as first line or second line systemic treatment option for SWI/SNF‐deficient DDEC/UEC that are also MMR protein‐deficient. Moreover, three recent studies have examined the expression of PD‐L1 in DDEC/UEC and all reported PD‐L1 expression in tumor and/or stromal immune cells in about half of the cases examined, which correlated with MMR deficiency status [34–36]. Early evidence also suggests that alterations within the SWI/SNF complex could be a predictive marker of response to checkpoint inhibitors [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Given the expanded indication for immunotherapy of MMR protein‐deficient tumors, immune check point inhibitors may be considered as first line or second line systemic treatment option for SWI/SNF‐deficient DDEC/UEC that are also MMR protein‐deficient. Moreover, three recent studies have examined the expression of PD‐L1 in DDEC/UEC and all reported PD‐L1 expression in tumor and/or stromal immune cells in about half of the cases examined, which correlated with MMR deficiency status [34–36]. Early evidence also suggests that alterations within the SWI/SNF complex could be a predictive marker of response to checkpoint inhibitors [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In Cohort 1 and Cohort 2, we explore the relation between radiomic features and PD1 expression at the protein-expression level and the gene level. The 2 types of endometrial carcinoma included in Cohort 1 could represent PD1-enriched cancer tissue and PD1-deficient cancer tissue ( 8 , 37 ). The radiomic feature of GLCMEntropy reveals a significant difference in PD1-enriched cancer tissue and PD1-deficient cancer tissue, regardless of the angle used.…”
Section: Discussionmentioning
confidence: 99%
“…DEC has recently garnered a lot of clinical and pathological attention with respect to cancer gene therapy. Recent studies have shown that the UC component in DEC is associated with the loss of MMR protein [ 7 ], suggesting an association between DEC and Lynch syndrome [ 1 ]. Some studies have evaluated MRI findings in patients with endometrial carcinoma with MMR deficiency [ 8 ], and genetic mutations causing MMR deficiency are also attracting attention in the field of radiology.…”
Section: Discussionmentioning
confidence: 99%